A Basic Study on Protective Steel Structures against Woody Debris Hazards. Issue 2 (June 2015) - Horiguchi, Toshiyuki; Shibuya, Hajime; Katsuki, Satoshi; Ishikawa, Nobutaka; Mizuyama, Takahisa
This paper presents a basic study for protective structures (slit dams) against woody debris hazards. First, a model experiment was carried out to examine the trap efficiency of a slit dam against woody debris with or without roots. Herein, the effects of length of woody debris, flow discharge and opening width of a slit dam on the trap efficiency were investigated. Second, a new three dimensional distinct element method (3D-DEM) was developed to simulate the trap efficiency of woody debris with or without roots by introducing cylindrical elements. Finally, the new 3D-DEM was applied to simulate an actual woody debris disaster site in Hiroshima, Japan.